2014
DOI: 10.1002/jclp.22082
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Variations in Suicidal Ideation and Behaviors: A Prominent Subtype Marked by Nonpsychiatric Factors Among Asian Americans

Abstract: Findings advance the culture and suicide literature by highlighting how current research and practice that characterize suicidal ideation and behaviors as a mental health phenomenon may not comprehensively identify suicidality among an ethnic minority group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…The results from the current study are consistent with Chia’s [26], who reported that a risk factor for young Chinese is mental illness, and congruent with the prevalence of a prior mental illness for suicide deaths in Singapore [50]. They also do not have religious beliefs with strong sanctions against suicide, consistent with a review of recent literature showing that religion is a common purveyor of cultural sanctions regarding the acceptability of suicides [5152]. …”
Section: Discussionsupporting
confidence: 90%
“…The results from the current study are consistent with Chia’s [26], who reported that a risk factor for young Chinese is mental illness, and congruent with the prevalence of a prior mental illness for suicide deaths in Singapore [50]. They also do not have religious beliefs with strong sanctions against suicide, consistent with a review of recent literature showing that religion is a common purveyor of cultural sanctions regarding the acceptability of suicides [5152]. …”
Section: Discussionsupporting
confidence: 90%
“…Additionally, though research typically has used mental illness (a conglomerate representation of cognitive, behavioral, and emotional factors) as one of the strongest indicators of suicide risk (Holma et al., ), emerging evidence suggests that some ethnic minorities may not experience suicide as a mental health phenomenon. Whereas 90% of suicide attempters in the general population have a psychiatric disorder, around 30% of Asian Americans with past attempts have no history of mental illness, and half of suicidal Asian Americans are characterized by a nonpsychiatric suicide subtype (Chu, Chi, Chen, & Leino, ).…”
Section: The Importance Of Cultural Meanings Of Suicidementioning
confidence: 99%
“…Although this sample was culturally diverse, they did not mention the cultural issues. This is surprising because different factors are related to suicide in different cultures (Chu, Chi, Chen, & Leino, 2014; Perez-Rodriguez et al., 2014). However, it may be that when faced with a suicidal person, the participants’ focus may have been on safety issues not on cultural risk and protective factors.…”
Section: Discussionmentioning
confidence: 99%